Pre-service and in-service teachers' perceptions on the integration of children's literature in mathematics teaching and learning in Ireland. Issue 2 (3rd April 2019) - Prendergast, Mark; Harbison, Lorraine; Miller, Sue; Trakulphadetkrai, Natthapoj Vincent
Abstract : The beneficial role that children's literature plays in facilitating the meaningful integration and advancement of literacy and numeracy in the primary mathematics classroom has been well validated by research findings internationally. In Ireland, supporting the development of literacy and numeracy is a key educational priority. Consequently, a myriad of policy initiatives such as the Literacy and Numeracy for Learning and Life strategy have been introduced. All aim to address concerns about young people's lack of basic literacy and numeracy skills and to consider new teaching and learning modalities to enhance same. Despite this, no official emphasis is given to incorporating literature in the Irish primary school mathematics curriculum. Therefore, it is pertinent and timely that this study seeks to ascertain pre-service and in-service teachers' views on the use of literature to support mathematics teaching and learning and to investigate perceived barriers to and enablers for the integration of children's literature in the mathematics classroom in Ireland. The analysis of the findings will be framed using Ajzen's (Ajzen, Icek. 1991. "The Theory of Planned Behavior." Organizational Behavior and Human Decision Processes 50 (2): 179–211) Theory of Planned Behavior (TPB) model. This research is part of a large international research collaboration (seewww.mathsthroughstories.org ), in which the beliefs of teachers with respect to children's literature are investigated.